Rancang Bangun Sistem Informasi Geografis Pemetaan Penduduk Menggunakan Metode Personal Extreme Programing (Studi Kasus : Desa Oro-Oro Ombo) - Firmansyah (Jurnal Repositor, 2023)
Abstract Oro-Oro Ombo village is a village in Batu District, Batu City, East Java province. Oro-Oro Ombo village is a village located in the District of Batu Kota Batu, approximately 2 km south of the Head Office of Batu. The process of inputting population data at Oro-Oro Ombo village office is still not controlled using information systems. The process of recording population data is still using Microsoft excel. The report submitted to the head of Community Welfare was obtained from inputting data from Microsoft excel which was captured and then used as a population report. The report will later be used as a decision-making. So it can take a decision to do the development in the village Oro-Oro Ombo. The purpose of this study is to develop PXP system in village managers. The development metode uses Personal extreme programming (PXP). Personal Extreme Programming is a development of extreme programming that can be used by a single developer. The system to be built in this study is an integrated system of village services. In conclusion, this PXP method can be implemented in this case study. The process begins with collecting needs, discussion with the client, then the client's needs are presented into user Stories. There are 5 user Stories. After getting the system needs, then do the development, planning consists of time estimation, priority, and determination of user Stories in each iteration.